Effectiveness of Chromolaena odorata as organic manure in promoting plant nutrient uptake and soil nutrient status on mustard rhizosphere. Issue 4 (July 2021) - Fikrinda, F; Akhmad, N; Ikhsan, W M
Abstract: Chromolaena odorata is an invasive plant that potentially organic manure. This study aimed to evaluate the effect of this weed on plant nutrient uptake and soil nutrient status on the mustard rhizosphere using a completely randomized block design and three replications. Factors examined were the organic manure types (green manure and compost) and doses (5, 10, 15, 20, and 25 Mg ha −1 ). The results showed that the compost was more effective than the green manure to improve potassium (K) uptake and soil nutrient (total nitrogen (N), available phosphor (P), and exchangeable K). Increasing doses of the organic manure until 25 mg ha −1 gave a better effect on N and K uptake and soil available P and exch. K but 20 Mg ha −1 on soil total N. The application of 25 mg ha −1 C. odorata as green manure gave more N and K content in the mustard. At the same time, 20 mg ha −1 compost increased soil available P. This study indicated that C. odorata could be developed as a good ameliorant either as green manure or compost to improve nutrient uptake mustard and soil nutrient status.